Study of polar thin ice clouds and aerosols seen by CloudSat and CALIPSO during midwinter 2007 - Grenier, Patrick; Blanchet, Jean‐Pierre; Muñoz‐Alpizar, Rodrigo (Journal of Geophysical Research: Atmospheres, 2009)
Data sets from CloudSat radar reflectivity and CALIPSO lidar backscattering measurements provide a new regard on Arctic and Antarctic winter cloud systems, as well as on the way aerosols determine their formation and evolution. Especially, links between the cloud ice crystal size and the surrounding aerosol field may be further investigated. In this study, the satellite observations are used to heuristically separate polar thin ice clouds into two crystal size categories, and an aerosol index based on the attenuated backscattering and color ratio of the sampled volumes is used for identifying haze in cloud‐free regions. Statistics from 386 Arctic satellite overpasses during January 2007 and from 379 overpasses over Antarctica during July 2007 reveal that sectors with the highest proportion of thin ice clouds having large ice crystals at their top are those for which the aerosol index is highest. Moreover, a weak but significant correlation between the cloud top ice effective radius and the above‐cloud aerosol index suggests that more polluted clouds tend to have higher ice effective radius, in 10 of the 11 sectors investigated. These results are interpreted in terms of a sulphate‐induced freezing inhibition effect.

Retrieving cloud optical depth and ice particle size using thermal and Far infrered radiometry in an Arctic environment - Blanchard, Yann; Royer, Alain; O'neill, Norman T.; Blanchet, Jean-Pierre (2009 IEEE International Geoscience and Remote Sensing Symposium, 2009)